Open Cholecystectomy in a 6 year old child - Zahid Hafeez, Muhammad Omar Ahmad, Saad Ahmad (Pakistan Journal of Medical & Health Sciences, 2024)
Cholelithiasis in children has increased in prevalence, ranging from 1.9% to 4%, due to childhood obesity and ultrasound use. Cholecystectomy is the treatment of choice for symptomatic gallstones, but expectant management is preferred for patients with longer periods of symptoms and longer timeframes between diagnosis and surgery. Laparoscopic cholecystectomy is safe, with lower postoperative complications and longer operative times compared to open approaches. Early diagnosis and surgery timing are crucial for timely treatment. Keywords: Cholecystectomy, childhood obesity, pediatric surgeons, case report, cholelithiasis